2013
DOI: 10.1124/dmd.112.050641
|View full text |Cite
|
Sign up to set email alerts
|

Decreased CYP3A Expression and Activity in Guinea Pig Models of Diet-Induced Metabolic Syndrome: Is Fatty Liver Infiltration Involved?

Abstract: Background: In humans, CYP3A drug-metabolizing enzyme subfamily is the most important. Numerous pathophysiological factors, such as diabetes and obesity, were shown to affect CYP3A activity. Often considered a precursor state for type II diabetes, metabolic syndrome exerts a modulating role on CYP3A, in our hypothesis. Objective: To evaluate the effect of metabolic syndrome on CYP3A drug-metabolizing activity/expression in guinea pigs. Methods: Hepatic microsomes were prepared from male Hartley guinea pigs fed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 25 publications
(28 reference statements)
1
18
0
Order By: Relevance
“…CYP3A metabolizes 50–60% of drugs available in the market [17] and is inhibited by fatty liver disease [79] and diabetes mellitus [80]. Because CYP3A plays such a prominent role in drug metabolism, changes in CYP3A expression and activity are crucial during the development of pharmaceuticals.…”
Section: Resultsmentioning
confidence: 99%
“…CYP3A metabolizes 50–60% of drugs available in the market [17] and is inhibited by fatty liver disease [79] and diabetes mellitus [80]. Because CYP3A plays such a prominent role in drug metabolism, changes in CYP3A expression and activity are crucial during the development of pharmaceuticals.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, liver transcriptomics analysis of mouse induced obesity models revealed a global dysregulation of Cyp genes, most notably in the Cyp3a and Cyp2c families [11]. Similar changes were also observed in diet-induced metabolic syndrome in guinea pigs, where decreases CYP3A expression and activity were observed in high-fat high-sucrose and high-fat high-fructose diets [25]. Downstream enzymes that metabolize norketamine, notably CYP2B6 and CYP2A6 could also be affected.…”
Section: Discussionmentioning
confidence: 96%
“…Fourth, different studies reported lower hepatic CYP3A4 activity during NAFLFD (Brill et al, 2012; Kolwankar et al, 2007; Patoine et al, 2013; Woolsey et al, 2015), but no mechanism has been proposed so far. In this study, CYP3A4 activity was reduced in HepaRG cells incubated with stearic acid but not with oleic acid.…”
Section: Discussionmentioning
confidence: 96%